Reliable Initial Trauma CT Findings of Supraclavicular Brachial Plexus Injury in Patients Sustaining Blunt Injuries - Povlow, M.R.; Davis, J.R.; Betts, A.M.; Clayton, S.M.; Cloran, F.J.; Aden, J.K.; Ritter, J.L. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Traumatic brachial plexus injuries are uncommon but can be debilitating. Early diagnosis is critical. Most patients undergo CT after trauma. We sought to identify correlative CT findings of supraclavicular brachial plexus injuries to discern who may require further evaluation with MR imaging and to measure multireviewer performance for their interpretations.MATERIALS AND METHODS: We identified all MR imaging examinations of the brachial plexus from our institution from January 2010 to January 2021 and included those performed for trauma. We excluded patients with penetrating or infraclavicular injuries and without preceding CTA of the neck or CT of the cervical spine. The cohort of 36 cases and 50 controls remained for analysis and were assessed for 6 findings: scalene muscle edema/enlargement, interscalene fat pad effacement, first rib fracture, cervical spine lateral mass/transverse process fracture, extra-axial cervical spinal hemorrhage, and cervical spinal cord eccentricity, forming a reference key. A resident physician and 2 neuroradiologists (blinded to the MR imaging) independently reviewed each CT scan for these findings. We measured agreement (Cohen κ) between observers and against the reference key.RESULTS: Interscalene fat pad effacement (sensitivity, specificity, 94.44%, 90.00%; OR = 130.33; P < .001) and scalene muscle edema/enlargement (sensitivity, specificity, 94.44%, 88.00%; OR = 153.00; P < .001) correlated significantly with brachial plexus injury. Agreement between observers and the key was almost perfect for those findings and fractures (pooled κ ≥ 0.84; P < .001). Agreement between observers was variable (κ = 0.48–0.97; P < .001).CONCLUSIONS: CT can accurately predict brachial plexus injuries, potentially enabling earlier definitive evaluation. High interobserver agreement suggests that findings are consistently learned and applied.BPIbrachial plexus injuries